APPROPRIATE PROCEDURES FOR SHARIA MICROFINANCING AT PT PERMODALAN NASIONAL MADANI MEKAAR SYARIAH - Nia Andria Erzah; Eva Susanti; Novita Sari; Muhammad Yusup; Retno Indri Yustika; Herlina; Ash Hatul Miftah (Fakultas Ekonomi Universitas Tridinanti Palembang, 2023)
PT. PNM Mekaar Syariah is an institution that distributes funds to the community to help economic development within households. Sharia microfinance is one of the tasks of sharia banks, especially independent sharia banks, namely by providing facilities for providing funds and meeting the needs of parties who lack funds for entrepreneurship. This research aims to find out what procedures are appropriate and appropriate formicrofinance at PT. PNM Mekaar Sharia. The research conducted by the researcher is qualitative research with a level of descriptive explanation. Data collection conducted by researchers using observation, interview and documentation techniques. This analysis, it can be concluded that, first, the procedure for implementing financing at PT. PNM Meekaar Syariah namely: Socialization (only for groups and new customers), Feasibility test, KK and KTP, Verification, Preparation of financing, Application of Mekaar Office disbursement funds to Financial Administration Offucer (FAO), Customer approval, Disbursement of financing , Payment is coordinated with the group leader or taken at the home of each customer and Financing uses a long period of time. Second, it can be concluded that the implementation of requirements at PT. PNM Mekaar Syariah has complied with Islamic law where in sharia microfinance has used murabahah contracts, wakalah contracts and wadiah contracts. And third, the procedures and implementation at PT. PNM Mekaar Syariah is not yet classified as an appropriate creteria because customers still have difficulties in financing and using a long time.